Density functional theory design of double donor dyes and electron transfer on dye/TiO2(101) composite systems for dye-sensitized solar cells. Issue 5 (13th January 2021) - Lin, Chundan; Liu, Yanbing; Shao, Di; Wang, Guochen; Xu, Huiying; Shao, Changjin; Zhang, Wansong; Yang, Zhenqing
Abstract : We designed a series of double donor organic dyes based on experimentally synthesized dye WD8, and further investigated their electronic structure, stability of the dye/TiO2 (101) systems, density of states (DOS) and absorption spectra using density functional theory (DFT). Abstract : In this work, we designed a series of double donor organic dyes, named ME101–ME106, based on experimentally synthesized dye WD8, and further investigated their electronic structure, the stability of the dye/TiO2 (101) systems, density of states (DOS) and absorption spectra using density functional theory (DFT) and time-dependent DFT (TDDFT). The molar extinction coefficients of all designed dyes are higher than WD8 . It's fascinating that ME106 exhibits a smallest energy gap and 75 nm redshifts compared to WD8 . The results of calculations reveal that ME101–ME106 /TiO2 (101) surfaces are more stable than WD8, double donor dyes have sufficient electron injection driving force and have very strong transfer electron ability. It is expected that the design of double donors can provide a new understanding and guidance for the investigation of high efficiency dye-sensitized devices.